Improving the Performance of the Touring Vehicle’s Stability System in Order to Reduce Vibrations by Using an Appropriate Control Unit - عربي قيس; جهاد بدور; حبيب محمود (Latakia University Journal -Engineering Sciences Series, 2023)
Through this research, the response of the four-wheel drive vehicle was studied and the dynamics of its suspension system analyzed according to different road conditions, whether flat or tilted, and the temporal and frequency response of the components of the suspension system was studied, with the aim of improving the ability to control the vehicle and its tilting system, and simulating the models and results via the Matlab platform. A number of results were reached, the most important of which are: - Reaching a damping constant value ranging between 3000÷ 2000 N/m. - Adding a new optimal and suitable control unit, which is adding the LQR controller. - Reaching a value of passenger comfort factor of 0.4. - Reaching a damping ratio located from 0.35 to 0.5